Estimation of the Sustainable Potential of Scads Fish (Decapterus spp) landed at the Belawan Ocean Fishing Port North Sumatra - Manik, Ave Ulina Putri; Yurleni, Yurleni; Soelistiowaty, Soelistiowaty (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
Scads fish (Decapterus spp.) is a fish that is widely consumed by the community so that consumer demand in the market is high for Scads Fish. Based on the Statistics book from the KKP, the catch of Scadsfish has decreased in catches from 2014 to 2016, this is due to continuous catching. The purpose of this study was to estimate the sustainable potential and to determine the level of utilization of Scads Fish in Belawan Ocean Fishing Port, North Sumatra. The research data was obtained from the Belawan Ocean Fishery Port in February 2021. The method used in this study is a survey method, using an equation model, namely Schaefer. The data analysis is a simple linear regression analysis using SPSS version 20. The sustainable potential of Scads Fish (Decapterus spp.) in the last 5 years is 16,526 tons/year with a utilization rate of 67.98% which is included in the catch density category and the number of fish catches allowed is 13,221 tons/year.